2013
DOI: 10.1016/j.buildenv.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Indoor environmental quality benefits of apartment energy retrofits

Abstract: Sixteen apartments serving low-income populations in three buildings were retrofit with the goal of simultaneously reducing energy consumption and improving indoor environmental quality (IEQ). Retrofit measures varied among apartments and included, among others, envelope sealing, installation of continuous mechanical ventilation systems, upgrading bathroom fans and range hoods, attic insulation, replacement of heating and cooling systems, and adding wall-mounted particle air cleaners. IEQ parameters were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(28 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…This value is obtained as the air exchange rate (k)accounting for entry from outdoors to indoorsdivided by the sum of the air exchange rate and indoor deposition rate (k + k d ), which is the rate at which NO 2 is removed from indoors. The value of 0.4 was estimated based on the consideration of published data on air exchange rates in California homes (Wilson et al, 1993(Wilson et al, , 1996Yamamoto et al, 2010) and reported NO 2 indoor deposition rates (Noris et al, 2013;Spicer et al, 1989Spicer et al, , 1993Wilson et al, 1986;Yang et al, 2004). Indoor NO X attributed to entry from outdoors was calculated as the sum of NO and NO 2 from outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…This value is obtained as the air exchange rate (k)accounting for entry from outdoors to indoorsdivided by the sum of the air exchange rate and indoor deposition rate (k + k d ), which is the rate at which NO 2 is removed from indoors. The value of 0.4 was estimated based on the consideration of published data on air exchange rates in California homes (Wilson et al, 1993(Wilson et al, , 1996Yamamoto et al, 2010) and reported NO 2 indoor deposition rates (Noris et al, 2013;Spicer et al, 1989Spicer et al, , 1993Wilson et al, 1986;Yang et al, 2004). Indoor NO X attributed to entry from outdoors was calculated as the sum of NO and NO 2 from outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…Most measurements of time-resolved PM 2.5 in homes have been made with photometers and optical particle counters. [25][26][27][28][29][30] Photometers measure the light scattered by the ensemble of particles and relate it to mass concentration via a calibration developed for a test aerosol. Particle counters analyze the scattering signals of individual particles and assign each to a size bin.…”
Section: Singer and Delpmentioning
confidence: 99%
“…Research efforts including both simulations and field measurements have demonstrated increased negative health effects or poor IAQ in efficient or retrofitted residences that did not sufficiently address IAQ provisions (Emmerich et al, 2005;Milner et al, 2014;Offermann, 2009;Wilson et al, 2013). Yet, other research efforts that have consistently included IAQ best practices have demonstrated improved health outcomes and generally reduced pollutant levels (Breysse et al, 2011;Jacobs, 2013;Kovesi et al, 2009;Leech et al, 2004;Noris et al, 2013a;Weichenthal et al, 2013). These mixed research findings substantiate the concerns of those who are concerned that efficiency may be implemented in residences without sufficient IAQ countermeasures.…”
Section: Additional Indoor Pollutantmentioning
confidence: 60%